Sex-specific troponin measures for diagnosis of acute coronary syndrome - Giannitsis, Evangelos (Heart, 2016)
The present article from Cullen et al 1 investigates the important question whether sex-specific cut-offs should be applied for prognostic purposes using high sensitivity cardiac troponin (cTn) assays. The article specifically addresses the effect of sex-specific cut-offs using the Architect high sensitivity troponin I assay (Abbott Diagnostics). The study enrolled 2841 patients from Australia, New Zealand and UK measuring hsTnI from frozen blood samples collected at presentation. The study applied the overall 99th centile value of a healthy reference population (26 ng/L) and sex-specific cut-offs for women (16 ng/L) and men (34 ng/L) as recommended by the manufacturer.2 A key finding of this study was that a sex-specific cut-off improved identification of women but not men at risk for myocardial infarction (MI), emergency coronary revascularisation or death within 1 year.1 In contrast, the effect of sex-specific cut-offs for more accurate diagnostic classification of suspected acute coronary syndrome (ACS) was not in the scope of this study and was found to minimally change the proportion of patients with hsTnI elevations from 9.29% with the overall cut-off to 9.15% by the use of sex-specific cut-offs. There was no significant overall net gain (NRI=−1.5%) in classification nor a net reclassification improvement for outcomes for the entire cohort for those with (NRI=−1.5%) or without major adverse cardiac events (MACE) at 1 year (NRI=−0.04%). Therefore, …
Gesehen am 09.06.2020